Spreading Sequence Design for Multiple Cell Synchronous DS-CDMA Systems under Total Weighted Squared Correlation Criterion. Issue 1 (29th July 2004) - Cotae, Paul
Abstract : An algorithm for designing spreading sequences for an overloaded multicellular synchronous DS-CDMA system on uplink is introduced. The criterion used to measure the optimality of the design is the total weighted square correlation (TWSC) assuming the channel state information known perfectly at both transmitter and receiver. By using this algorithm it is possible to obtain orthogonal generalized WBE sequences sets for any processing gain. The bandwidth of initial generalized WBE signals of each cell is preserved in the extended signal space associated to multicellular system. Mathematical formalism is illustrated by selected numerical examples.